Efforts to Improve Student Activities and Results in Integrated Learning Using the Problem Based Model Learning at SDN 060924 District Sanding Field - Aswan Simanjuntak; Hidayat (PT Inovasi Pratama Internasional, 2023)
This study aims to determine efforts to increase student activity and learning outcomes in learning multiplication with integers using the problem-based learning model at SDN 060924, Medan Amplas District. This research is a classroom action research. The model used in this study is the Spiral model from Kemmis & Mc Taggart. This research was conducted in May 2023 at SDN 060924 Medan Amplas. In this study using a test instrument, namely multiple choice questions as many as 15 questions and non-tes, namely in the form of observation sheets, interviews, and documentation. There are several types of data collection techniques, namely tests, observations, and documentation. Based on the table about the development of student learning activities above, it shows an increase in student learning activities. In this case, the average increase in student learning activity in each aspect is 11,345% and all aspects of the activity reach the active criteria. Learning mathematics about integer material in cycles I, II and III that the application of problem based learning has in fact experienced an increase of 90% from the number of students who complete it in cycles I, II and III, the description of student learning activities regarding multiplication of integers increases greatly Good. It is known that the mastery of the mathematics learning results of class IV students on mixed arithmetic operations material reaches 90%, so that it meets the specified indicator of 70%. So in this case the researcher can be said to be successful and there is no need for further action in the next cycle. Observations from observers showed an increase in student activity in participating in learning.